Effectiveness of Interventions Promoting HIV Serostatus Disclosure to Sexual Partners: A Systematic Review - Conserve, Donaldson F. (AIDS Behav, 2015)
Disclosure of HIV serostatus to sexual partners is mandated within certain states in the United States and other countries. Despite these laws implemented and public health efforts to increase disclosure, rates of disclosure to sexual partners among people living with HIV (PLWH) remain low, suggesting the need for interventions to assist PLWH with the disclosure process. We conducted a systematic review of studies testing whether HIV serostatus disclosure interventions increase disclosure to sexual partners. We searched six electronic databases and screened 484 records. Five studies published between 2005 and 2012 met inclusion criteria and were included in this review. Results showed that three of the HIV serostatus disclosure-related intervention studies were efficacious in promoting disclosure to sexual partners. Although all three studies were conducted in the United States the intervention content and measurements of disclosure across the studies varied, so broad conclusions are not possible. The findings suggest that more rigorous HIV serostatus disclosure-related intervention trials targeting different populations in the United States and abroad are needed to facilitate disclosure to sexual partners.